Monitoreo y morfometría de la avifauna del campus de la Universidad del Valle (2011-2012), Valle del Cauca, Colombia (2015)
Given the increasing urban development and loss of forest areas which have an important ecological role in maintaining regional and continental bird populations there is a need to increase our knowledge about these population changes in order to understand their internal dynamics. From September 2011 to May 2012 birds occurring at the Universidad del Valle were monitored as part of the project “Use of the habitat by transcontinental migratory birds in Universidad del Valle’s Campus”. The information was obtained by observation transects, mist nets, and focal tracking of individuals. A total of 1995 records were obtained, represented in 12 orders, 29 families, and 76 species. The family with the highest number of species was Tyrannidae (14), followed by Thraupidae (eight) and Parulidae (eight). Fourteen species of Nearctic migratory birds were captured and banded. This information constitutes one of the few records of morphology obtained for resident and migratory birds in urban areas in Colombia.